High prevalence of gastrointestinal manifestations among Cytomegalovirus end-organ disease in the combination antiretroviral era - Margaret R. Caplan; Eleanor M.P. Wilson; Melissa Schechter; Catherine W. Cai; Allison Venner; Rachel Bishop; Joseph Adelsberger; Jeanette Higgins; Gregg Roby; Jing Wang; Virginia Sheikh; Irini Sereti (Elsevier, 2021)
Background: Cytomegalovirus (CMV) end-organ disease (EOD) continues to pose a significant risk to patients with advanced HIV disease despite decreased incidence with combination anti-retroviral therapy (ART) and lower mortality with effective anti-CMV therapy. Subclinical CMV shedding may also contribute to ongoing inflammation and non-infectious comorbidities. Methods: We examined the occurrence of CMV EOD and CMV shedding in a cohort of patients participating in a prospective observational study of severely immunosuppressed (CD4 ≤100 cells/μl), ART-naïve, HIV-1 infected adult participants. Results: We studied 206 participants, of whom 193 (93.7%) were CMV IgG positive. Twenty-five participants (12.1%) developed confirmed CMV EOD. At baseline, 47 (22.8%) had CMV viremia detectable by PCR in the absence of clinical disease (CMV viremia). The remaining 134 (65%) had neither CMV EOD nor CMV viremia detected at baseline. Five participants with CMV EOD (2.4% of total cohort, 20% of CMV EOD) met AIDS Clinical Trials Group criteria for CMV immune reconstitution inflammatory syndrome (IRIS). Only one-third of CMV EOD patients had retinitis, while two-thirds presented with histologically confirmed gastrointestinal illness. CMV viremia was associated with higher percentages of activated CD8+ T cells even after HIV suppression. Conclusion: The manifestations of CMV EOD in advanced HIV disease before and after initiation of ART may be more diverse than previously described, with high incidence of gastrointestinal illness. Recognition and treatment of unusual clinical presentations of CMV infection remains important in reducing morbidity and mortality from HIV co-infections.